2009
DOI: 10.1111/j.1365-2648.2009.05068.x
|View full text |Cite
|
Sign up to set email alerts
|

Community health: an evolutionary concept analysis

Abstract: The definition derived from the concept analysis of community health makes explicit the importance of community-based participatory action in local health improvement processes. Identification of the attributes of community health will enhance communication across disciplines involved in community health practice, research and education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 62 publications
0
13
0
4
Order By: Relevance
“…Second, to effectively develop ACP as a health promoting practice, community palliative care services need to engage with local communities, including communities of practice. As anticipated, the inclusion of community engagement in the Model provided opportunity for the services to connect more closely with their local community (Baisch 2009). The strategies initiated by the services were consistent with a health promoting palliative care approach (Rosenberg & Yates 2010, Seymour et al.…”
Section: Discussionmentioning
confidence: 89%
“…Second, to effectively develop ACP as a health promoting practice, community palliative care services need to engage with local communities, including communities of practice. As anticipated, the inclusion of community engagement in the Model provided opportunity for the services to connect more closely with their local community (Baisch 2009). The strategies initiated by the services were consistent with a health promoting palliative care approach (Rosenberg & Yates 2010, Seymour et al.…”
Section: Discussionmentioning
confidence: 89%
“…Concept analysis is a research strategy involving categorisation and discrimination among terms through which a set of attributes or characteristics essential to the meaning of the terms are clearly identified (Baisch, 2009;Xyrichis & Ream, 2008). A clinician who is not an expert in the violence domain would learn about different types of violence and contributory factors.…”
Section: Ensuring That the Research Topic And Methods Are Appropriatementioning
confidence: 99%
“…Conceptual analysis is an indepth, critical, exploration of the meaning of specific ideas. To further clarify concepts and relationships among them, a conceptual analysis could be used in the early research phases (Baisch, 2009;Xyrichis & Ream, 2008). The following concepts could be fruitfully analysed: rights, responsibilities, obligations, justice, safety, power, and authority.…”
Section: Ensuring the Methodology Is Appropriate To Address The Topicmentioning
confidence: 99%
“…Nursing researchers have also found that utilizing a collaborative approach better ensures that a unique definition of “community health” will be established locally and democratically (Baisch, 2009). While we applied principles of conducting research, we were not seeking to fill a gap in the literature by asking specific research questions.…”
Section: Case Study Methodsmentioning
confidence: 99%